(untitled) (The Reasoner, 2025)
Hykel Hosni interviews Kenneth Aizawa, Professor of Philosophy of Science at Rutgers University, Newark. The interview opens with Aizawa’s reflections on the challenges currently confronting U.S. universities under the second Trump administration. It then turns to a discussion of his forthcoming book, Compositional Abduction and Scientific Interpretation: A Granular Approach. Following a retrospective on Aizawa’s academic trajectory, the conversation concludes with his advice for early-stage researchers.